2016
DOI: 10.3390/nu8050294
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Nutrition and Symptoms: Nutritional Survey of Children with Autism Spectrum Disorder in Chongqing, China

Abstract: Restricted diets and inadequate nutrient intake of children with autism spectrum disorder (ASD) have been reported. This study examined the nutritional statuses of children with ASD and the relationships between their behaviors and nutritional intake. A total of 154 children with ASD (age = 5.21 ± 1.83 years) and 73 typically-developing (TD) children (age = 4.83 ± 0.84 years) from Chongqing, China, were enrolled. The severity of ASD was evaluated using the Childhood Autism Rating Scale (CARS). The serum ferrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
2
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 59 publications
4
88
2
24
Order By: Relevance
“…We investigated the effect of vitamin D 3 supplementation (2000 IU/day) for 20 weeks among a small sample of urban, mostly Caucasian children with clinician-diagnosed ASD at high latitude over winter season. In contrast to most11 26 27 but not all previous reports,21 there was no difference between VDD and VDS groups regarding ASD parameters at baseline. There was a significant increase in vitamin D status in the D 3 group.…”
Section: Discussioncontrasting
confidence: 93%
“…We investigated the effect of vitamin D 3 supplementation (2000 IU/day) for 20 weeks among a small sample of urban, mostly Caucasian children with clinician-diagnosed ASD at high latitude over winter season. In contrast to most11 26 27 but not all previous reports,21 there was no difference between VDD and VDS groups regarding ASD parameters at baseline. There was a significant increase in vitamin D status in the D 3 group.…”
Section: Discussioncontrasting
confidence: 93%
“…Studies in the final sample for analysis were categorised by type of disability. 'Neurodevelopmental' disability was the largest category, containing nine studies (53%) [38][39][40][41][42][43][44][45]. There were five studies that considered multiple disability diagnoses, but that reported data overall for children with disabilities as a group, so were included in a 'general disability' (29%) category.…”
Section: Resultsmentioning
confidence: 99%
“…Em um estudo comparativo, realizado com crianças com TEA e sem TEA atendidas em um hospital no Norte da Índia, observou-se que as crianças com TEA apresentaram aversão a frutas e vegetais (17) . Estudos apontam que as crianças com TEA têm preferências por alimentos a base de amido, lanches e alimentos ultraprocessados, e apresentam relutância ao consumo de frutas e vegetais (18)(19)(20) .…”
Section: Discussionunclassified